2008
DOI: 10.1002/hon.861
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated VEGFR2/KDR receptors are widely expressed in B‐cell non‐Hodgkin's lymphomas and correlate with hypoxia inducible factor activation

Abstract: The expression of hypoxia inducible factors (HIF) 1alpha and 2alpha, of vascular endothelial growth factor (VEGF) and of the phosphorylated form of its receptor VEGFR2 (pVEGFR2/KDR) were investigated immunohistochemically in a series of 146 B-cell non-Hodgkin's lymphomas and 48 normal lymph nodes. These proteins were significantly up-regulated in neoplastic lymphocytes and a significantly higher expression of HIF1alpha (p = 0.05), VEGF (p = 0.02) and pVEGFR2/KDR (p = 0.007) was recorded in diffuse large B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 34 publications
2
18
0
1
Order By: Relevance
“…Expression of HIF1a mRNA and protein in ALK þ TCL cells As the expression of the HIF1a protein has been identified in a large spectrum of malignancies including several types of B-cell lymphomas (Evens et al, 2008;Giatromanolaki et al, 2008;Passam et al, 2009), we asked whether this is also the case in ALK þ TCL cells. Immunohistochemical analysis of tissue samples from 10 ALK þ TCL cases revealed that malignant-appearing anaplastic, ALK-expressing lymphoma cells also expressed HIF1a in all the cases examined ( Figure 1a, upper panels; representative images).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of HIF1a mRNA and protein in ALK þ TCL cells As the expression of the HIF1a protein has been identified in a large spectrum of malignancies including several types of B-cell lymphomas (Evens et al, 2008;Giatromanolaki et al, 2008;Passam et al, 2009), we asked whether this is also the case in ALK þ TCL cells. Immunohistochemical analysis of tissue samples from 10 ALK þ TCL cases revealed that malignant-appearing anaplastic, ALK-expressing lymphoma cells also expressed HIF1a in all the cases examined ( Figure 1a, upper panels; representative images).…”
Section: Resultsmentioning
confidence: 99%
“…Although HIF1a expression has been identified in the whole spectrum of malignancies including several types of B-cell lymphomas (Evens et al, 2008;Giatromanolaki et al, 2008;Passam et al, 2009), the mechanisms regulating its expression, in particular on the mRNA level, still remain only partially understood. Our findings support the model that although cell oxygenation status tightly regulates expression of the HIF1a protein by impairing its degradation under hypoxia, oncogenic proteins such as NPM/ALK induce its synthesis by activating the HIF1a gene.…”
Section: Npm/alk-stat3 Pathway Induces Hif1a Expression M Marzec Et Almentioning
confidence: 99%
“…62,63 To date, aberrant expression of HIF-1a and/or HIF-2a has been documented in cancers of the brain, colon, lung, breast, prostate, kidney, pancreas, cervix, bladder and ovary, [64][65][66][67][68][69] and overexpression of both HIFs has been found to indicate a highly aggressive disease phenotype associated with poor prognosis. [70][71][72][73][74][75][76] Whereas examination of aberrant HIF expression has largely been restricted to solid tumors, recent studies have reported that HIF-1a and HIF-2a are also overexpressed in hematological malignancies such as diffuse large B-cell lymphoma, 77,78 chronic lymphocytic leukemia 79 and acute lymphoblastic leukemia. 80 Although HIF-1a and HIF-2a show 48% amino-acid sequence homology and have similar protein structures and oxygendependent mechanisms of regulation, there are a growing number of physiological and mechanistic differences between these proteins, which indicates that they possess distinct, nonredundant roles.…”
Section: Hypoxia and Cancermentioning
confidence: 99%
“…The role of a defective pVHL causing increased VEGF expression may provide a potential explanation for this association. Furthermore, the correlation between HIF activation and VEGF receptor activation in B-cell lymphomas has been well documented in a paper published by Giatromanolaki et al [18]. This study examined the expression of the phosphorylated and thereby activated form of VEGF receptor 2 (KDR) in patients with B-cell non-Hodgkin's lymphoma.…”
Section: Resultsmentioning
confidence: 95%